Accuracy of Endoscopic Ultrasonography for Determining the Depth of Invasion in Early Gastric Cancer - Kim, Seung-Jun; Lim, Chul-Hyun; Lee, Bo-In (Turkish Journal of Gastroenterology, 2022)
Background: Accurate staging for depth of invasion (T stage) of early gastric cancer is critical for determining the treatment modality. Endoscopic ultrasonography is a reliable method for assessing the T stage. However, its diagnostic accuracy varies. The aim of this study is to investigate clinicopathologic factors affecting the diagnostic accuracy of endoscopic ultrasonography in early gastric cancer. Methods: Patients with early gastric cancer who had undergone endoscopic resection or gastrectomy were included. The diagnostic accuracy of endoscopic ultrasonography was evaluated by comparing the T stage by endoscopic ultrasonography with histopathology of the resected specimen. Subgroup analysis was performed according to the endoscopic resection criteria. Results: A total of 223 early gastric cancer lesions were included. The overall accuracy of endoscopic ultrasonography for T staging was 66.4%. The diagnostic accuracy for lesions ≤2 cm was significantly higher than for those of 2-3 cm (odds ratio 3.59) or those >3 cm (odds ratio 5.47). The diagnostic accuracy was significantly decreased in lesions with ulceration (odds ratio 2.62) or non-flat morphology (odds ratio 2.94). The accuracy of endoscopic ultrasonography for lesions corresponding to the absolute endoscopic resection criteria was significantly higher than for those corresponding to the expanded criteria (97.3% vs 71.9%, P = .002). Of the tumors that were overestimated by endoscopic ultrasonography treated with gastrectomy, 93.3% corresponded to the expanded criteria. Conclusion: Endoscopic ultrasonography had poor accuracy in early gastric cancer lesions larger than 2 cm, those with ulceration, and those with non-flat morphology, that is, lesions corresponding to the expanded criteria were more frequently overstaged by endoscopic ultrasonography. Such early gastric cancers should be carefully considered when staging by endoscopic ultrasonography before gastrectomy Cite this article as: Kim SJ, Lim CH, Lee BI. Accuracy of endoscopic ultrasonography for determining the depth of invasion in early gastric cancer. Turk J Gastroenterol. 2022;33(9):785-792.